Modelo matemático de asignación y elaboración de horarios con rotación de aulas de clase para los cursos de secundaria en un colegio privado en la ciudad de Bogotá (2020)
This article considers a real problem of scheduling classes and Assignment of classrooms for secondary courses for the Calasanz school, Bogotá Colombia. This problem is characterized by implementing an integer programming model, where the complexity generated by the large number of decision variables and their respective constraints is synthesized by dividing the input data, resulting in two runs of the model with minor modifications inside. The first run was carried out with the input data of the sixth to ninth grade (6 to 9) with their respective restrictions and assignments, and for the second run, it was taken as input data both the tenth and eleventh grade requirements (10 and 11) and the assignment established in the first run, in order to balance the complexity of the models and thus be able to find a solution to the problem. This resolution method is validated, through the implementation of the real data of the second academic semester of the year 2019 provided by the institution, regarding the academic load of these courses for this period of the year. After obtaining the two groups of assignments, it was evident that the subjects that were dictated en bloc did not consider the assignment of the same room for this union. By For this reason, it was decided to develop two macros that will carry out this change of rooms without the initial assignment of subjects, teachers, courses, days and time slots was affected. In this way, the final result of the investigative process was each of the schedules weekly for courses from sixth to eleven, taking into account their respective subjects, teachers and the availability of classrooms in each of the time slots of their day student. In addition to this, it was possible to consolidate the working hours of the teachers who teach high school courses, providing a practical, complete and efficient solution to the initially encountered scheduling problem. Keywords: Schedule scheduling, integer scheduling, Timetabling, Method exact, approximate method, macros.